Resurfacing memories: Mnemonic and tactile representations of family history in the making of new heirlooms - Forlano, Penelope; Smith, Dianne (Interstices: Journal of Architecture and Related Arts, 2016)
Supervisor: Dianne Smith By taking a design anthropology approach in my PhD studies, I have critically examined post-acquisition behaviour of custodians and their inalienable objects to inform a new framework for the design of enduring, or ‘heirloom’, objects. Specifically, this creative project demonstrates an alternative view to mainstream design discourse and instead suggests that the intangible, that is an individual’s personal memory and experience, can be tangibly embedded into the object by the designer in a textural and visually representative way. The physically mnemonic characteristic of the creative work; therefore increases its potential to become an inalienable heirloom.